Otimização e aplicação de testes rápidos para a detecção de Carbapenemases em bactérias gram-negativas - Silva, Ana Carolina Ramos Da [UNIFESP] (2019)
Antimicrobial resistance has become one of the most important public health concerns. Carbapenems characterize one of the last therapeutic options for the treatment of multidrug resistant (MDR) gram-negative bacteria; however, the frequency of pathogens with ability of hydrolysing carbapenems, as well as co-producing other resistance mechanisms has increased significantly worldwide. Rapid diagnosis for detection of carbapenemase producers have a high impact on decreasing mortality and morbidity rates, as well as reducing hospital costs. Thus, the aim of this study was to optimize and evaluate rapid tests for detecting carbapenemases in gram-negative bacteria. Our scientific article 1 evaluated the influence of different culture media for the detection of carbapenemases hydrolytic capacity by the MALDI TOF MS technique. We observed that three isolates of A. baumanni producing OXA-25, OXA-26 and OXA-72 showed false negative results after growth on MacConkey agar, while all isolates evaluated after growth on CPS, Blood and Mueller-Hinton agar were detected within 4 hours of incubation. Our second study (scientific article 2) evaluated the KPC K-SeT immunochromatographic device for detecting different KPC variants, as well as the influence of distinct culture media on this assay. The test proved to be a fast and sensitive tool for detecting different KPC variants within a maximum of 15 minutes. However, the bacterial inoculum of two KPC-6 and KPC-8 producing Enterobacteriaceae was increased to enable detection by KPC K-SeT. In addition, the EasyQ KPC molecular test was evaluated for the detection of blaKPC directly from rectal swabs, resulting in the third scientific manuscript. The test demonstrated 100% sensitivity and 87.7% specificity and the blaKPC detection was performed directly from the rectal swab without prior incubation. Finally, our last study (scientific article 4) evaluated the ability of the MALDI TOF MS to detect ceftazidime-avibactam (CAZ/AVI) hydrolysis among carbapenemase producing isolates. This study demonstrated high agreement with the molecular method (97%) and the sensitivity test (94%). Our results demonstrated that most of the evaluated methodologies demonstrated fast turn around time and high sensitivity and specificity rates. However, the workflow of each clinical laboratory should be evaluated to determine the phenotypic and/or molecular test that best suits the specific characteristics of each medical center.